The Relocation of the Canons Regular Monastery in Żagań as an Element in the Reform of Interior Life - Zbigniew Witczak (Folia Historica Cracoviensia, 2019)
The location in which a church was based played an important role in the life of religious communities in the Middle Ages. Interactions with society and the mutual influence of a monastery on the surrounding societies could support or inhibit the development of an abbey. There were situations when monks were moved to serve in different locations. In Silesia, we have two examples of canons regular monasteries. Both the monastery of the Blessed Virgin Mary in Wrocław and the convent of Żagań were originally located in other places. As described in the monastery chronicle, the transfer of the monastery from Nowogród Bobrzański to Żagań in 1284 was an event that opened new opportunities and perspectives for the abbey.